An automated dose verification software for brachytherapy - Wang, Xianliang (J Contemp Brachytherapy, 2018)
PURPOSE: To report an implementation method and the results of independent brachytherapy dose verification software (DVS). MATERIAL AND METHODS: The DVS was developed based on Visual C++ and adopted a modular structure design. The DICOM RT files exported from a treatment planning system (TPS) were automatically loaded into the DVS. The DVS used the TG-43 formalism for dose calculation. A total of 15 cervical cancer patients who underwent brachytherapy were retrospectively selected to test the DVS. Dosimetric parameters and γ analysis (0.1 cm, 5%) were used to evaluate the dose differences between the DVS and the TPS. RESULTS: Compared with the TPS dose, the γ pass rates of the dose calculated by the DVS were higher than 98%. For the clinical target volume (CTV), the dosimetric differences were less than 0.63% for D(90%) and D(100%). For the bladder, rectum, and sigmoid, the agreement of D(0.1cc), D(1cc), and D(2cc) were within a 0.78% level. CONCLUSIONS: With minimal human-computer interactions, the DVS can verify the accuracy of doses calculated by the TPS.